Metropolitan time: Reflections on the millenium, calendars, and Gregorian hegemony - Bernward Joerges (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2000)
The official beginning of the new Millennium, bureaucratically correct on January 1, 2001, gives occasion to reconsider the meanings of that divide in time celebrated globally a while ago. A year into the new century, one is still hard put, in our part of the world, to find public utterances that do not in some way evoke the great watershed of 2000. Although the urgency has dwindled, the habit acquired during the decade or so of running up to the Millennium perseveres: everything that has a sense of time - the past, the present, the future -tends to be couched in terms of the great divide. In this discussion paper, a wide range of issues related to the millennial turn as a major phenomenon in (Gregorian) macro-time is addressed, both at the level of chronology as a subject matter in social studies and at the level of chronology as an organizing feature of social studies of science and technology. – – Der offizielle Beginn des neuen Jahrtausends, bürokratisch korrekt am 1. Januar 2001, gibt Anlass dazu, die Bedeutungen der grossen Zeitenwende noch einmal zu überdenken, die kürzlich weltweit gefeiert wurde. Ein Jahr nach dem Ereignis fällt es immer noch schwer, öffentliche Äußerungen zu finden, die nicht in der einen oder anderen Weise Bezug nehmen auf die Wasserscheide 2000. Die Dringlichkeit mag nachgelassen haben, aber die im Lauf des Countdown zum Millennium erworbene Gewohnheit hält an, alles und jedes, was mit einem Zeitsinn versehen ist, auf diese Wende zu beziehen. In diesem Diskussionspapier wird eine breite Palette von Themen angesprochen, die mit dem Jahrtausendwechsel als einem überragenden Phänomen unserer Gregorianischen Zeitrechnung zu tun haben, sowohl auf der Ebene von Chronologien als Gegenständen von sozialwissenschaftlicher Forschung als auch auf der Ebene von Chronologien als organisierenden Medien in sozialwissenschaftlicher Forschung.
Keywords: 300